2021
DOI: 10.1016/j.jpubeco.2021.104406
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of linking permit markets

Abstract: This paper presents a novel benefit of linking emission permit markets. We let countries issue permits non-cooperatively, and with endogenous technology we show there are gains from permit trade even if countries are identical. Linking the permit markets of different countries will turn permit issuance into intertemporal strategic complements. The intertemporal strategic complementarity arises because issuing fewer permits today increases investments in green energy capacity in all permit market countries, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Furthermore, the presence of an international carbon market with endogenous permit choice (Helm 2003;Holtsmark and Weitzman 2020) incentivises regions with low abatement costs to mitigate emissions and sell permits, which can reduce global emissions and raise global welfare. This has been shown for an exogenous carbon market with an endogenous climate coalition (Altamirano-Cabrera and Finus 2006;Lessmann et al 2014), an endogenous carbon market without climate coalition (Carbone et al 2009;Holtsmark and Midttømme 2021) and an endogenous carbon market with an endogenous climate coalition (Yu and Wu 2022). 3 Further examples include Kotchen and Moore (2007) and Ziegler (2020) [Engler et al (2022) and Andre et al (2024)], who find that altruistic values are significantly positively correlated with participation in green-electricity programs [pro-climate donations].…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, the presence of an international carbon market with endogenous permit choice (Helm 2003;Holtsmark and Weitzman 2020) incentivises regions with low abatement costs to mitigate emissions and sell permits, which can reduce global emissions and raise global welfare. This has been shown for an exogenous carbon market with an endogenous climate coalition (Altamirano-Cabrera and Finus 2006;Lessmann et al 2014), an endogenous carbon market without climate coalition (Carbone et al 2009;Holtsmark and Midttømme 2021) and an endogenous carbon market with an endogenous climate coalition (Yu and Wu 2022). 3 Further examples include Kotchen and Moore (2007) and Ziegler (2020) [Engler et al (2022) and Andre et al (2024)], who find that altruistic values are significantly positively correlated with participation in green-electricity programs [pro-climate donations].…”
Section: Introductionmentioning
confidence: 85%
“…Helm and Pichler [10] analyzed technology transfer between more developed and less developed countries, and concluded that a joint system of technology transfer and permit trading can lead to lower overall emissions and the efficiency gains on the permit market. Holtsmark and Midttømme [11] showed that linking of permit markets leads to an increased investment in green energy capacity in all permit market jurisdictions, and jurisdictions with a higher green energy capacity respond by issuing fewer permits in the future. Antoniou et al [12] showed benefits of permit markets linkage in a two-jurisdiction model under a symmetric scenario; however, in the asymmetric case the linkage may fail to form.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, there is a body of literature that investigates the effects of market linkage on emissions in the context of C&T. While aggregate emissions during a compliance period are determined exogenously in a C&T, linking allowance markets can have intertemporal impacts on emissions. Holtsmark and Midttømme (2021) find that integrating allowance markets across countries can reduce emissions if countries strategically adjust their future emission caps in response to market linkage, while Lapan and Sikdar (2019) argue that linking allowance markets across countries weakens the incentives for tightening national emission caps. This work makes several important contributions.…”
Section: Introductionmentioning
confidence: 99%